In vitro Digestion and Swelling Kinetics of Thymoquinone-Loaded Pickering Emulsions Incorporated in Alginate-Chitosan Hydrogel Beads - Wong, See Kiat; Lawrencia, Dora; Supramaniam, Janarthanan; Goh, Bey Hing; Manickam, Sivakumar; Wong, Tin Wui; Pang, Cheng Heng; Tang, Siah Ying (Frontiers in Nutrition, 2021)
The present work aimed to investigate the swelling behavior, in vitro digestion, and release of a hydrophobic bioactive compound, thymoquinone (TQ), loaded in Pickering emulsion incorporated in alginate-chitosan hydrogel beads using a simulated gastrointestinal model. In this study, oil-in-water Pickering emulsions of uniform micron droplet sizes were formulated using 20% red palm olein and 0.5% (w/v) cellulose nanocrystals-soy protein isolate (CNC/SPI) complex followed by encapsulation within beads. FT-IR was used to characterize the bonding between the alginate, chitosan and Pickering emulsion. 2% (w/v) alginate-1% (w/v) chitosan hydrogel beads were found to be spherical with higher stability against structural deformation. The alginate-chitosan beads displayed excellent stability in simulated gastric fluid (SGF) with a low water uptake of ~ 19%. The hydrogel beads demonstrated a high swelling degree (85%) with a superior water uptake capacity of ~593% during intestinal digestion in simulated intestinal fluid (SIF). After exposure to SIF, the microstructure transformation was observed, causing erosion and degradation of alginate/chitosan wall materials. The release profile of TQ up to 83% was achieved in intestinal digestion, and the release behaviour was dominated by diffusion via the bead swelling process. These results provided useful insight into the design of food-grade colloidal delivery systems using protein-polysaccharide complex-stabilized Pickering emulsions incorporated in alginate-chitosan hydrogel beads.